Molecular Mechanism of Germinated Foxtail Millet Bioactive Peptides in Attenuating Copper-induced Oxidative Damage in Caenorhabditis elegans - Huiqi ZHANG; Xiao CHEN; Xueling JIN; Jingjing LI; Juanli YUAN; Jinyan GAO; Hongbing CHEN; Yong WU (Shipin gongye ke-ji)
Objective: This study aimed to explore the mitigating effects of germinated foxtail millet bioactive peptides (GRBPs) on copper-induced oxidative damage in Caenorhabditis elegans (C. elegans) and its potential mechanisms. Methods: By randomly grouping, the wild-type N2 C. elegans were divided into a control group and GRBPs groups to examine the effects of GRBPs feeding on mobility and survival rate of C. elegans induced by copper. The impact of GRBPs on oxidative damage was assessed by measuring the levels of reactive oxygen species (ROS), glutathione (GSH), and the activities of catalase (CAT), and superoxide dismutase (SOD). Furthermore, the mechanism of action of GRBPs was explored through genomic and transcriptomic sequencing techniques (RNA-seq) and untargeted metabolomics analysis. Antioxidant-related genes were validated by reverse transcription and real-time quantitative PCR (qPCR). Results: GRBPs obviously improved the survival rate and mobility of C. elegans after copper treatment, and a concentration of 1 mg/mL of GRBPs extremely significantly reduced the levels of MDA (P<0.0001), increased the activities of CAT and SOD, and regulated the expression of specific genes (such as upregulation of ctl-1, ctl-2, and downregulation of sod-1, sod-2). At the genetic level, GRBPs mainly regulated the structural constituent of cuticle and the expression of genes related to cytochrome enzyme P450 in C. elegans. At the metabolic level, GRBPs mainly regulated the content of biosynthesis of plant secondary metabolites in C. elegans. Conclusions: This study demonstrates that germinated millet bioactive peptides can effectively alleviate copper-induced oxidative damage, possibly through enhancing the activity of antioxidant enzymes, reducing the expression of cuticle and cytochrome enzyme P450 related genes, and regulating the content of plant secondary metabolites.